Supporting women entrepreneurs in Tunisia - Imed Drine; Mouna Grach (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Whether policy support should be designed differently for women entrepreneurs is a particularly relevant question. To answer this, and to inform the design of policies to provide appropriate support for women entrepreneurs, the paper compares male and female perceptions of typical entrepreneurship support services, such as government provision of information, training and funding. The focus is on Tunisia, a developing country characterized by high level of unemployment, particularly of women. Based on a survey of 50 men and 50 women entrepreneurs in the regions of Sfax, Sousse and Tunis, our results suggest that existing support services are inadequate for promoting female entrepreneurship. Accordingly we discuss support measures specifically designed for women entrepreneurs.
Keywords: L26; M13; J16; Z13; 330; entrepreneurship; gender; women entrepreneurs; Africa